1986
DOI: 10.1107/s0108767386099956
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the photoelectron emission probability with inclined X-ray Laue diffraction

Abstract: A simple relation has been established between the Fourier component of the probability density P(z) of photoelectron emission from different depths of a crystal and the angular dependence of the emission of photoelectrons formed in inclined X-ray Laue diffraction, which for the first time permitted the use of a direct method for the reconstruction of the P(z) function. Accurate measurements of the angular dependence of photoelectron emission were carried out on a silicon single crystal with diffraction of Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The highest energy band ͑6.2ഛ E ഛ 6.9 keV͒, containing mainly lowenergy-loss Si K-photoelectrons with an associated escape depth L = 65 nm, 14 was used in the present experiments. Owing to a relatively low implantation depth, the x-ray diffraction measurements were carried out by a triple crystal diffractometer ͑TCD͒ with a Si double reflection monochromator for selecting the Cu K␣ 1 radiation as a probe and a high quality Si analyzer crystal, both ͓001͔ oriented.…”
Section: Methodsmentioning
confidence: 99%
“…The highest energy band ͑6.2ഛ E ഛ 6.9 keV͒, containing mainly lowenergy-loss Si K-photoelectrons with an associated escape depth L = 65 nm, 14 was used in the present experiments. Owing to a relatively low implantation depth, the x-ray diffraction measurements were carried out by a triple crystal diffractometer ͑TCD͒ with a Si double reflection monochromator for selecting the Cu K␣ 1 radiation as a probe and a high quality Si analyzer crystal, both ͓001͔ oriented.…”
Section: Methodsmentioning
confidence: 99%
“…The XRSW experiments were performed using the above mentioned geometry and the emitted electrons were measured using a special detector described elsewhere. 9 Briefly, the sample was mounted inside a gas-flow proportional counter provided with mylar windows transparent for x-rays. The XRP signal was recorded by a gold-plated tungsten wire 20 m in diameter and parallel to the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of experimentally reconstructed P(z) functions showed that for low-energy-loss photoelectrons (high-energy side of the emission spectrum) with the smallest escape depth, a simple exponential function provides a satisfactory approximation (Afanas'ev et al, 1986),…”
Section: Escape Depth Of Photoelectronsmentioning
confidence: 99%
“…The most important question in the quantitative analysis of XSW data is the reliability of the values of the photoelectron escape depths. In general, the problem of the determination of the P(z) function is rather complicated (Thomas et al, 1975;Liljequist et al, 1978;Afanas'ev et al, 1986). The P(z) function depends not only on the characteristics of the material under investigation, but also on the experimental setup (energy resolution, angular divergences, etc.…”
Section: Introductionmentioning
confidence: 99%